2015
DOI: 10.1590/0004-282x20150111
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological profile of patients diagnosed with multiple sclerosis in João Pessoa, Paraíba, Brazil

Abstract: Prevalence rates of multiple sclerosis (MS) suggest an interrelationship between genetic and environmental factors, ranging worldwide.Objectives Clinical and epidemiological characterization of MS patients in João Pessoa, Paraíba city.Methods Study involving patients treated in five services in the city.Results It included 87 patients with MS, representing a prevalence of 12.0 cases/100,000 population, mainly women (77%) and white people (66.7%) with mean age of 43 years and average age of the first outbreak o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 16 publications
1
9
0
7
Order By: Relevance
“…However, studies from different parts of the world have also found mean EDSS scores of around 2 and 3. A Brazil study found that the EDSS score was 3.50±1.9, 37 while a study of newly diagnosed MS from Qatar found a mean EDSS score of 2.4 (median=2), reflecting a lower level of clinical progression despite a higher radiological burden, 38 and a study of 200 MS cases from Iran found that the EDSS score was 2.1±1.9. 13 None of our patients had an EDSS score higher than 7.5 because patients with higher disability scores are bedridden, receives supportive treatment only.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies from different parts of the world have also found mean EDSS scores of around 2 and 3. A Brazil study found that the EDSS score was 3.50±1.9, 37 while a study of newly diagnosed MS from Qatar found a mean EDSS score of 2.4 (median=2), reflecting a lower level of clinical progression despite a higher radiological burden, 38 and a study of 200 MS cases from Iran found that the EDSS score was 2.1±1.9. 13 None of our patients had an EDSS score higher than 7.5 because patients with higher disability scores are bedridden, receives supportive treatment only.…”
Section: Discussionmentioning
confidence: 99%
“…Daha önceki bildirilmiş çalışmalarda MS hastalarının büyük çoğunluğunun interferon beta kullandıkları tespit edilmiştir 26 , bizim çalışmamızda da hastalarımızın çoğunluğu interferon beta kullanıyorken, %29,2 gibi ciddi bir orandaki hasta grubu ise ilaç kullanmamaktaydı. Ancak son yıllarda hızla artan immunmodülatu-ar tedavi alternatifleri, şu anki interferonların kullanım ve tolerasyon zorlukları düşünüldüğünde, ilerleyen yıl-larda bu oranların ciddi şekilde değişebileceğini ve ilaç kullanmayan hasta grubunun önemli oranda düşeceği-ni düşündürmektedir.…”
Section: Materyal Ve Metot: çAlışmaya Dahil Edilen 210 Hastanın 126'sunclassified
“… 11 Negreiros et al developed a neuropsychological battery to identify cognitive impairment in Brazilian patients with RRMS and concluded that the COWAT and the RAVLT had adequate sensitivity and specificity to discriminate RRMS patients from controls. 17 Here, the visuospatial domain was assessed with the aid of the VOT, because this test was validated in Brazil. 24…”
Section: Methodsmentioning
confidence: 99%
“…However, the neuropsychological profile of Brazilian MS patients is relatively unknown. 17 Unfortunately, the clinical utility of these tests remains to be demonstrated in the incipient phases of MS especially in patients from Latin-American countries.…”
Section: Introductionmentioning
confidence: 99%